Assessing the Rise in Papillary Thyroid Cancer Incidence: A 38-Year Australian Study Investigating WHO Classification Influence - Steven Weller; Cordia Chu; Alfred King-yin Lam (Journal of Epidemiology and Global Health)
Abstract The incidence of thyroid cancer has shown marked increases globally over recent decades. This study investigated how the incidence of papillary thyroid carcinoma (PTC) subtypes and World Health Organisation (WHO) endocrine tumour classification changes have affected overall thyroid cancer incidence recorded in Australia. Using incidence data from the Australian Institute of Health and Welfare cancer registry (spanning 1982 to 2019), this descriptive epidemiological study employed joinpoint regression analysis to assess temporal trends in thyroid carcinoma incidence, focusing on PTC. Results were then compared with WHO endocrine tumour classification changes over the same period. The results showed increasing trends for the classic PTC subtype over the entire 38-year period and for thyroid microcarcinomas post-2003, while a declining trend for the follicular variant of PTC was observed commencing in 2015. Examination of PTC incidence also revealed distinct changes in trends that align with the WHO classification of papillary microcarcinoma as a subtype in 2004 and the reclassification of some encapsulated follicular variant of PTCs to non-invasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTP) in 2016/17. Even when taking these WHO classification changes into account, significant increases in PTC over the last three decades are observed. These findings underscore the shifts in classification driven by improving diagnostic clarity influencing thyroid carcinoma incidence patterns. However, thyroid carcinoma cases in Australia have dramatically increased over the last three decades independent of WHO classification changes, suggesting a genuine increase rather than simply being a direct consequence of improved reporting and diagnostics.